2016
DOI: 10.2147/clep.s99021
|View full text |Cite
|
Sign up to set email alerts
|

Stage-specific survival and recurrence in patients with cutaneous malignant melanoma in Europe – a systematic review of the literature

Abstract: BackgroundGiven the increasing incidence in cutaneous malignant melanoma (CMM) and the recent changes in the treatment landscape, it is important to understand stage-specific overall and recurrence-free survival patterns in Europe. Despite publications such as EUROCARE-5, there is limited information on stage-specific survival for CMM in Europe.MethodWe carried out a systematic literature review to provide an up-to-date summary of stage-specific survival and recurrence-free survival patterns in patients with C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
70
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(84 citation statements)
references
References 43 publications
11
70
1
2
Order By: Relevance
“…Long-term survival depends on the tumor stage [28], the response to systemic treatment, the surgical resection options and the pre-existing comorbidity of the patient. Due to new therapeutic techniques including tyrosine kinase inhibitors and checkpoint inhibitors, five year survival increased to 37% [29].…”
Section: Discussionmentioning
confidence: 99%
“…Long-term survival depends on the tumor stage [28], the response to systemic treatment, the surgical resection options and the pre-existing comorbidity of the patient. Due to new therapeutic techniques including tyrosine kinase inhibitors and checkpoint inhibitors, five year survival increased to 37% [29].…”
Section: Discussionmentioning
confidence: 99%
“…A recent paper looking at the global picture of melanoma shows that the greatest burden falls on New Zealand, Australia and Europe, and on older people and men (Karimkhani et al, 2017). Information on survival by stage has been limited for skin melanoma; a systematic literature review that included studies from 9 countries in Europe found that the reported 5 year overall survival varies: 95%-100% (stage I), 65%-92.8% (stage II), 41%-71% (stage III), and 9%-28% (stage IV), and concluded that there are large variations in stage-specific overall and recurrence-free survival by study type and by country (Svedman et al, 2016). Despite new treatments, advanced melanoma still has a poor prognosis.…”
Section: Melanoma: Key Facts and Challengesmentioning
confidence: 99%
“…In 2017, an estimated 87 110 patients will be newly diagnosed with melanoma in the United States while 9 730 persons will die of the disease . Surgical resection is the mainstay of therapy . Unfortunately, there are many challenges associated with the management of malignant melanoma.…”
Section: Introductionmentioning
confidence: 99%